Mmetuta Usorookwu Na Echiche N'asusu Igbo (2013)
This paper examines inflection in the Imilike dialect of the Igbo language with emphasis on the verb inflection. The study adopts a descriptive approach based on surface structure analysis. Verbs were inflected for tense/aspect, mood and polarity in Imilike. The paper reveals that some inflectional affixes and strategies of achieving inflection in the dialect when compared with the standard Igbo and consequently influences the choice of affixes used to achieve inflection of verbs. The dialect employs strategies such as the optional use of the Open vowel prefix a/e, affix sequencing and more of the role suffixation to achieve inflection in the dialect. Tone plays a significant role in achieving inflection in the dialect as in the standard Igbo. The study points to the profound insight available from the study of various Igbo dialects.